The fourth enemy [large type] - Perry, Anne (Perry, Anne. Daniel Pitt novel, 2023)
"Working his way up at London law firm fford Croft and Gibson, Daniel Pitt is named junior counsel on a fraud case with the potential to make or break his reputation. The trouble is, Malcolm Vayne, the man on trial, has deep pockets, and even deeper connections. Working alongside Gideon Hunter, the new head of his firm, Daniel must find a way to prove that Vayne is guilty. Vayne's trial reveals his deep political ambitions, and it heats up further when a crucial witness is found dead. When another witness is kidnapped, Daniel must set out on a rescue mission that puts his life--and the case against Vayne--in peril" --